Artificial Norms and the Influence of the Mass Media - Kenny, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This exercise is designed to give students the opportunity to analyze the content of one popular program in order to determine whether elements of the mass media are designed to alter or reinforce their existing socio-political attitudes. In this case, the program being examined is an episode of the HBO series Six Feet Under. A wide variety of other programs could also be used for the exercise (Friends, Will and Grace, Judging Amy, The O.C., etc.). An interesting variation on this exercise is to have students do a similar but contrasting analysis on two programs from different eras (e.g., comparing the content of an episode of I Love Lucy or Father Knows Best with an episode of Friends or Will and Grace). This exercise is suitable for a range of classes, including Introduction to Sociology, Social Psychology, Social Organization, and Deviance. I personally use it in a course on social organization/social structure, in a section devoted to exploring macro-level social influences on individual behavior.